Auditory frequency discrimination in developmental dyslexia: A meta‐analysis - Witton, Caroline (Dyslexia, 2019)
Auditory frequency discrimination has been used as an index of sensory processing in developmental language disorders such as dyslexia, where group differences have often been interpreted as evidence for a basic deficit in auditory processing that underpins and constrains individual variability in the development of phonological skills. Here, we conducted a meta‐analysis to evaluate the cumulative evidence for group differences in frequency discrimination and to explore the impact of some potential moderator variables that could contribute to variability in effect‐size estimations across studies. Our analyses revealed mean effect sizes for group differences on frequency discrimination tasks on the order of three‐quarters of a standard deviation, but in the presence of substantial inter‐study variability in their magnitude. Moderator variable analyses indicated that factors related both to participant variability on behavioural and cognitive variables associated with the dyslexia phenotype, and to variability in the task design, contributed to differences in the magnitude of effect size across studies. The apparently complex pattern of results was compounded by the lack of concurrent, standardised metrics of cognitive and reading component skills across the constituent studies. Differences on sensory processing tasks are often reported in studies of developmental disorders, but these need to be more carefully interpreted in the context of non‐sensory factors, which may explain significant inter‐ and intra‐group variance in the dependent measure of interest.